KEBENARAN TUHAN DI DALAM AL-QUR’AN - Anam, Dimisqi Chaerul (MAGHZA, 2016)
This writing is try to explain and proven the truth of Kalam Muhammad in Quran especially al mukminun : 12-14 verses. Two important things in this explanation are first , theory of science is not wrong and some part of them have relevancy with quran. Modern science find the synchronizationof qur’an in the step of creat human embryo whereas quran was arrival in 7 century. Secondly the truth of quran as wahyu which the contain and meaning had been impossible could be done by people in the seven century so there is no suspicion with quran.